GROWTH RATE OF BODY CIRCUMFERENCE OF MALE BALI CATTLE DURING FATTENING - Rambu Raya Malicha Rajah; I Putu Sampurna; I Wayan Wirata (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Bali cattle are native Indonesian germplasm originating from the island of Bali, and are widely kept by farmers due to their many advantages. Growth can be assessed as an increase in height, length, weight, and body circumference, which occurs in young cattle. This study aims to determine the growth rate of body circumference of male Balinese cattle during fattening and to describe the growth of muscle and fat in the cattle's body. A total of 20 male Balinese cows aged 11-22 months were used as research samples. Data were collected using saturated sampling technique, namely measuring the body circumference of fattened male Balinese cattle in Abdi Pertiwi Livestock Farmer Group, Gerokgak, Buleleng. The data obtained were analyzed with power regression analysis to determine the growth rate of body size of Balinese cattle. The results of power regression analysis showed that the overall correlation coefficient was very significant (p<0.05) in each size of front neck circumference, back neck circumference, chest circumference and hip circumference of male Balinese cattle. Each dimension of body circumference has a different growth rate. Based on these results, it can be concluded that there are differences in the growth rate of body circumference of male Balinese cattle during fattening. The growth rate of body circumference of male balinese cattle shows that the back neck circumference and front neck circumference have higher growth potential than hip circumference and chest circumference.